The Impact of Task Variety, Career Promotion, And Reward to Agricultural Extension Worker’s Performance - Rochaeni, Siti; Ludiin, Muchlis R; Ramly, Mansyur (Archives of Business Research, 2019)
In order to develop the quality of human resource in agriculture, a presence of agricultural extension workers – who were professional, creative, innovative, dan have global insight – in performing a agricultural extension that productive, effective, and efficient. The performance of agricultural extension workers had a strategic position in agricultural development. Thus, they had a lot of variety in job. The ability to perform their job were influenced by both internal and external factors. The internal factors include the characteristic of agricultural extension worker, educational background, and working experience that formed their behaviour. The external factors such as wages or rewards and career promotion of agricultural extension worker. When the rewards can meet their needs, a high level of task variety could be done. It is also expected that if the career or functional position being promoted, the performance of agricultural extension worker would also increase. Hence, career promotion may have influence to agricultural extension worker’s performance. The purposes of this research were to analyse both the direct and indirect impact of task variety, reward, and career promotion to performance. The research conducted through survey using interview and fill up questionnaire. Using the design of structural equation model of factors that influence the performance of agricultural extension worker, the data was analysed using model Structural Equation Models (SEM) with software Smart PLS 3.2.7 ver. Results of the research was: (1) there were a direct impact of task variety to performance, and indirect impact through career promotion and reward; (2) there were a direct impact of career promotion to performance, and indirect impact through task variety and reward; (3) there were a direct impact of reward to performance, and indirect impact through task variety and career promotion.